2005
DOI: 10.1128/iai.73.12.7853-7859.2005
|View full text |Cite
|
Sign up to set email alerts
|

Decreased In Situ Expression of Interleukin-10 Receptor Is Correlated with the Exacerbated Inflammatory and Cytotoxic Responses Observed in Mucosal Leishmaniasis

Abstract: Human infection with Leishmania braziliensis can lead to cutaneous leishmaniasis (CL) or mucosal leishmaniasis (ML). We hypothesize that the intense tissue destruction observed in ML is a consequence of an uncontrolled exacerbated inflammatory immune response, with cytotoxic activity. For the first time, this work identifies the cellular sources of inflammatory and antiinflammatory cytokines, the expression of effector molecules, and the expression of interleukin-10 (IL-10) receptor in ML and CL lesions by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
213
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(229 citation statements)
references
References 35 publications
13
213
2
1
Order By: Relevance
“…The role of IL-4 in LCL is not clear, as there is no report of a strong polarization toward Th2 in LCL subjects. PBMC from MCL patients produce less IL-10, respond less to IL-10 and TGF-␤ (20), and show lower IL-10 receptor expression than PBMCs from LCL subjects (23). These findings suggest that MCL might be aggravated by uncontrolled Th1 mediated inflammation due to low IL-10 and TGF-␤ production.…”
Section: Immunological and Genetic Evidence For A Crucial Role Of Il-mentioning
confidence: 61%
See 1 more Smart Citation
“…The role of IL-4 in LCL is not clear, as there is no report of a strong polarization toward Th2 in LCL subjects. PBMC from MCL patients produce less IL-10, respond less to IL-10 and TGF-␤ (20), and show lower IL-10 receptor expression than PBMCs from LCL subjects (23). These findings suggest that MCL might be aggravated by uncontrolled Th1 mediated inflammation due to low IL-10 and TGF-␤ production.…”
Section: Immunological and Genetic Evidence For A Crucial Role Of Il-mentioning
confidence: 61%
“…Studies on nonhealing lesions as a result of L. mexicana infection have shown an association with increased IL-10 and TGF-␤ production (24) in the presence of IFN-␥; this suggests that IFN-␥ is neutralized by IL-10 and/or TGF-␤. Severe and rare MCL disease was associated with low IL-10 and TGF-␤ production (20) and lower IL-10 receptor expression than that observed in LCL (23). Thus, the role of IL-10 in human CL, as a result of Lb infection, was less clear.…”
Section: Discussionmentioning
confidence: 83%
“…23,24 Therefore, it is an imbalance between pro-inflammatory and regulatory cytokines that leads to ATL pathogenesis. 23,32,33 Herein, we showed that elderly subjects have a decrease in the antigen-response of IFNγ, and thus lack the main cytokine responsible for macrophage activation and killing. Furthermore, we also observed an increase in IL-10 that may facilitate parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal forms are characterized by an exacerbated cell-mediated immune response and high intralesional levels of TNF-␣, IFN-␥, and IL-4, leading to extensive tissue destruction but not to parasite clearance (3,5,34,47). A defect in IL-10 receptor expression was shown to correlate with high inflammatory responses in ML (14). Finally, T reg cells and high IL-10 production potential have been described in the skin of individuals infected with L. braziliensis (10).…”
mentioning
confidence: 99%